Gut microbiota and pancreatic cancer risk, and the mediating role of immune cells and inflammatory cytokines: a Mendelian randomization study - Chen, Zhiting; Wang, Zhe; Bao, Hejing; Ma, Shudong (Frontiers in Immunology, 2024)
Introduction Gut microbiota (GM) influences the occurrence and development of pancreatic cancer (PC), potentially through the involvement of inflammatory cytokines (IC) and immune cells (IM). We aimed to investigate the causal impact of the gut microbiota (GM) on pancreatic cancer (PC) and identify potential IC and IM mediators. Methods The summary statistics data from whole-genome association studies of gut microbiota, immune cells, inflammatory cytokines, and four types of pancreatic tumors (MNP: Malignant neoplasm of pancreas; BNP: Benign neoplasm of pancreas; ADCP: Adenocarcinoma and ductal carcinoma of pancreas; NTCP: Neuroendocrine tumor and carcinoma of pancreas). Two-sample univariable Mendelian randomization (UVMR), multivariable Mendelian randomization (MVMR), and mediation analysis were employed to assess the causal relationship between gut microbiota (GM) and pancreatic cancer (PC), as well as potential IC and IM mediators. Results The two-sample UVMR analysis showed causal relationships between 20 gut microbiota species and pancreatic cancer, with pancreatic cancer affecting the abundance of 37 gut microbiota species. Mediation analysis revealed that Interleukin-6 (IL-6), “CD4 on naive CD4+ T cell” and “SSC-A on HLA DR+ Natural Killer” mediated the causal effects of gut microbiota on pancreatic cancer. Conclusion This Mendelian randomization study demonstrates causal relationships between several specific gut microbiota and pancreatic cancer, as well as potential mediators (IC, IM).